Cannabis Use Is Associated With Decreased Antiretroviral Therapy Adherence Among Older Adults With HIV. (5th January 2023) - Manuzak, Jennifer A; Granche, Janeway; Tassiopoulos, Katherine; Rower, Joseph E; Knox, Justin R; Williams, Dionna W; Ellis, Ronald J; Goodkin, Karl; Sharma, Anjali; Erlandson, Kristine M
Abstract: Background: Conflicting evidence exists on the impact of cannabis use on antiretroviral therapy (ART) adherence among people with human immunodeficiency virus (PWH). We leveraged data collected among older PWH to characterize longitudinal associations between cannabis use and ART adherence. Methods: AIDS Clinical Trials Group (ACTG) A5322 study participants were categorized as <100% (≥1 missed dose in past 7 days) or 100% (no missed doses) ART adherent. Participants self-reported current (past month), intermittent (past year but not past month), and no cannabis (in past year) use at each study visit. Generalized linear models using generalized estimating equations were fit and inverse probability weighting was used to adjust for time-varying confounders and loss to follow-up. Results: Among 1011 participants (median age, 51 years), 18% reported current, 6% intermittent, and 76% no cannabis use at baseline; 88% reported 100% ART adherence. Current cannabis users were more likely to be <100% adherent than nonusers (adjusted risk ratio [aRR], 1.53 [95% CI, 1.11–2.10]). There was no association between ART adherence and current versus intermittent (aRR, 1.39 [95% CI, .85–2.28]) or intermittent versus no cannabis use (aRR, 1.04 [95% CI, .62–1.73]). Conclusions: Among a cohort of older PWH, current cannabis users had a higher risk of <100% ART adherence compared to nonusers. These findings have important clinical implications as suboptimal ART adherence is associated with ART drug resistance, virologic failure, and elevated risk for mortality. Further research is needed to elucidate the mechanisms by which cannabis use decreases ART adherence in older PWH and to advance the development of more efficacious methods to mitigate nonadherence in this vulnerable population. Abstract : Among older (≥40 years old) people with HIV participating in the AIDS Clinical Trials Group A5322 (HAILO) study, current cannabis users were less likely to be 100% antiretroviral therapy adherent as compared to non-cannabis-using study participants.